Mechanism and Target Therapy of Rituximab in Systemic Lupus Erythematosus: Literature Review - Listiadewi, Afifah; Suharjono (Pharmacon: Jurnal Farmasi Indonesia, 2025)
The malignant condition known as lymphoma affects the lymphoid tissues, bone marrow, and blood. Between 2009 and 2013, the incidence rate of lymphoma in the United States was approximately 22 per 100,000 individuals. Hemolytic anemia, leukopenia, and thrombocytopenia are among the hematologic symptoms of systemic lupus erythematosus (SLE), a highly diverse disease. Rituximab (RTU) and other monoclonal antibodies that target β cells are used as off-label therapy for SLE. Rituximab is a human CD20-specific chimeric monoclonal antibody. Rituximab can be utilized as an alternate therapy for SLE in addition to providing treatment for lymphoma. Rituximab has demonstrated positive effects and potential as a treatment for SLE in several clinical trials. This study aims to elucidate the mechanism of action of rituximab as a therapeutic agent targeting β cells in patients with SLE. The methodology used in this study is a literature review. The literature retrieval and search strategies were conducted using electronic means. A literature review of seven periodicals was produced by employing keywords to retrieve scientific material using the Boolean approach. Rituximab depletes and inhibits the activation of β cells in individuals with systemic lupus erythematosus by binding to the Fc gamma IIβ receptor on both β cells and macrophages.